Growth and diversification in New Zealand's agriservice industry : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Geography at Massey University - Campbell, Colin Terence (Massey University, 1979)
The thesis has been designed to research the problem of how the stock and station companies have developed from single product or single function firms and then evolved into large diversified mercantile corporations. The hypothesis surmises that the firms have followed trends in the growth of other large overseas companies which has meant changes in function, structure and especially unique to this industry, spatial changes. The geographic nature of the problem is centred on the companies expansion through time and space in the New Zealand economy. In studying this topic it is necessary to comprehend the basic components of corporate growth, diversification and the uniquity of the agriservice industry, a 'colonial invention' (MacDonald, 1975) of Australasia. In order to conceptualise the geography of the problem a model has been utilised to illustrate the spatial changes that agriservice companies have undergone when competing for space over New Zealand. The model, figure 1.1. refers to the thresholds of development, requirements that have to be met by a firm in order to increase its operating space. This change in scale results in an increase of activities and the organisational scale of the firm over time.
Keywords: New Zealand; Agricultural industries